Improved vaccines for the control of East Coast Fever: IPSR Innovation Profile - Lacasta, Anna; Nene, Vishvanath M.; Lovel, Jonathan; King, Neil; Mwangi, Thumbi (2022)
The assessment of an experimental vaccine for the control of East Coast fever (ECF). Thelieria parva, the causative agent of ECF, is a killer parasite infecting cattle. The experimental vaccine is based on the use of nanoparticles to present and deliver p67C antigen. In future the vaccine will be developed by an animal health company and used by livestock keepers to significantly reduce morbidity and mortality in their cattle herds. The new technology will also validate the nanoparticle platform for the delivery of subunit vaccines for livestock.